Endovascular Treatment of Internal Carotid Artery Bifurcation Aneurysms: A Single-Center Experience and a Systematic Review and Meta-Analysis - Morales-Valero, S.F.; Brinjikji, W.; Murad, M.H.; Wald, J.T.; Lanzino, G. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Endovascular coiling of internal carotid artery bifurcation aneurysms can be challenging due to unfavorable morphologic features. With improvements in endovascular techniques, several series have detailed the results and complications of endovascular treatment of aneurysms at this location. We performed a systematic review and meta-analysis of published series on the endovascular treatment of ICA bifurcation aneurysms, including a tertiary referral center experience. MATERIALS AND METHODS: We performed a comprehensive literature search for reports on contemporary endovascular treatment of ICA bifurcation aneurysms from 2000 to 2013, and we reviewed our experience. We extracted information regarding periprocedural complications, procedure-related morbidity and mortality, immediate angiographic outcome, long-term clinical and angiographic outcome, and retreatment rate. Event rates were pooled across studies by using random-effects meta-analysis. RESULTS: Including our series of 37 patients, 6 studies with 158 patients were analyzed. Approximately 60% of the aneurysms presented as unruptured; 88.0% (95% CI, 68.0%–96.0%) of aneurysms showed complete or near-complete occlusion at immediate postoperative angiography compared with 82.0% (95% CI, 73.0%–88.0%) at last follow-up. The procedure-related morbidity and mortality were 3.0% (95% CI, 1.0%–7.0%) and 3.0% (95% CI, 1.0%–8.0%), respectively. The retreatment rate was 14.0% (95% CI, 8.0%–25.0%). Good neurologic outcome was achieved in 93.0% (95% CI, 86.0%–97.0%) of patients. CONCLUSIONS: Endovascular treatment of ICA bifurcation aneurysms is feasible and effective and is associated with high immediate angiographic occlusion rates. However, retreatment rates and procedure-related morbidity and mortality are non-negligible.